Analisis Transformasi Kemandirian Belajar melalui Media Digital Interaktif: Transformation Analysis of Learning Independence through Interactive Digital Media - Lilis Setianawati; Najlatun Naqiyah; Mochamad Nursalim (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2023)
This study aims to examine how interactive digital mediacan transform students' learning independence, especially atthe secondary education level. Learning independence is the ability of studentsto organize, motivate, and evaluate themselves in the learning process withoutdepending on others. In the digital era, the role of learning media is notonly as a tool, but also as a facilitator that helps studentsLearn actively, flexibly, and independently. The research method usedThis research is a qualitative study with a descriptive approach.through literature review from various relevant current scientific sources.The results show that the use of interactive digital mediacontributes positively to the transformation of learning independence becauseprovides a learning experience that is personalized, interesting, and can be accessed anytimeaccording to student needs. In addition, digital media encourages active engagement, self-reflection, and exploration-based learning. TheImplications of this research emphasize the importance of digital media integration inlearning strategies to shape the character of learners who are independent, adaptive, andready to face challenges in the technological era.